Targeted transarterial embolization of the femoral head: development of a minimally invasive approach to model Legg-Calvé-Perthes disease in piglets - Susan A. Novotny; Jennifer C. Laine; Casey P. Johnson; Alexandra R. Armstrong; Erick O. Buko; Ashton A. Amann; Reza Talaie; Ferenc Tóth (PLoS ONE, 2025)
Clinical management of children with Legg-Calvé-Perthes Disease (LCPD) is hampered by incomplete understanding of how the extent of ischemic injury and the duration and quality of subsequent repair determine patient outcome. The traditional piglet model of LCPD is limited to capturing global femoral head ischemia; thus, a new model is needed in which the extent of ischemia can be varied to replicate the spectrum of disease seen in children. In this exploratory study, we used an iterative approach to test and refine methods to bilaterally occlude vessels supplying the femoral heads in n = 8 young piglets under angiographic control. The deep and/or acetabular medial femoral circumflex arteries (DMFCA and AMFCA) were identified and embolized using either embolic particles or liquid embolic agents. The extent of ischemia was assessed immediately post-embolization (4 piglets) and/or 7 days following embolization (7 piglets) using contrast-enhanced magnetic resonance imaging (CE-MRI). After the final CE-MRI, piglets were euthanized, and their femora were harvested for histologic evaluation. Embolization of the DMFCA alone caused transient ischemia that largely resolved by 7 days with small regions of fibrovascular repair of ischemic injury remaining on histology. Embolization of both the DMFCA and AMFCA resulted in a greater degree of pathologic changes at 7 days post-operatively, but also with nearly complete restoration of femoral head perfusion. We found that combining injection of embolic particles with subsequent placement of an embolic micro-coil was the most effective approach to induce ischemic injury, which may be aided in larger piglets. While our findings should be interpreted cautiously due to the wide range in the age and size of animals investigated, they demonstrate that transarterial embolization of the vascular supply of the femoral head results in transient ischemia and histological changes consistent with partial ischemic injury. These results will inform further development of a minimally invasive piglet model of LCPD that offers a unique representation of the spectrum of pathophysiology of LCPD compared to the traditional model.